PENGEMBANGAN WISATA KULINER DI KOTA SEMARANG - Tinus Lis Indrianto, Agoes; Tourism; Anna Kristanti, Dwi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
ABSTRACT In addition to the tourism industry's explosive growth, Semarang City hosts a large number of visitors who come to savor the local cuisine. The purpose of this study is to discover culinary tourism destinations in Semarang City and to ascertain the typical cuisine of the city, which attracts tourists. This study also examines the traits of visitors to Semarang City in relation to the development of the culinary arts. This study uses a survey approach and is descriptive quantitative research. employing incidental sampling, a non-probability sampling approach, on a sample of one hundred respondents. Several culinary districts are included in the research location. The findings indicated that the numerous gastronomic attractions in Semarang draw visitors. Among the delectable dishes are Nasi Kucing, Mie Kopyok, Tahu Gimbal, and Soto Semarang. Lunpia, Wingko Babat, and Bandeng Presto are examples of side dishes. Gilo-Gilo, Blanggem, Tahu Petis, and Gandos are examples of snacks. The five locations that make up Semarang City's culinary are Taman KB, jl. MT. Haryono, jl. Pandanaran, intersection five, and Sri Ratu Mall. The majority of visitors are between the ages of 31 and 35, have completed high school, and work as public servants. Most of the guests are from outside the city and are female. They travel with relatives and gather knowledge from friends and family. Keywords: Semarang City, tourism development, culinary tourism.